57 THE IMPACT OF HORMONAL CONTRACEPTIVES ON SERUM ANDROGEN LEVELS AND SEXUAL FUNCTION IN PREMENOPAUSAL WOMEN. (1st January 2005) - Zhu, A. L.; Johnson, C. E.; Berman, J.; Sarajari, S.
Abstract : Sexual dysfunction, associated with low libido, vaginal dryness, impaired orgasm, and decreased arousal has been reported in about 15% of oral contraceptive users. It has been noted that these sexual side effects are the result of changes in serum androgen profiles caused by the use of oral contraceptives. The goal of this study is to examine the relationship between changes in serum androgen profiles and specific sexual function complaints. This was a retrospective questionnaire-based study. The subjects studied were determined via a set of inclusion/exclusion criteria from reviewing charts of all patients evaluated at the UCLA Female Sexual Medicine Center. Previously collected data on patients' serum androgen profiles (total testosterone, free testosterone, sex hormone binding globulin) and sexual health questionnaires (regarding sexual function, level of sexual distress, and sexual desire/energy) both before and after the discontinuation of oral contraceptive usage were extracted from the charts of qualified subjects. A total of 21 women were evaluated. Median total testosterone and free testosterone levels increased significantly, while SHBG decreased. The free androgen index (FAI= total T/SHBG) increased from 0.139 to 0.474 (p ≤ 0.001). Questionnaire data showed a significant increase in sexual energy (2 to 4, p = 0.002), decrease in sexual distress (36 to 25, p = 0.017) and improvement in global Female Sexual Function Index (FSFI) score (15.4 to 23.3, p = 0.003). Therefore, hormonal contraceptives is a potential cause of sexual dysfunction in pre-menopausal women and the underlying etiology is mostly likely related to increased SHBG and decreased total and free testosterone levels.